Strategi Guru Mata Pelajaran IPS dalam Menanamkan Karakter Disiplin dan Tanggungjawab pada Santri Kelas VIII di Pesantren Salafiyah Alkhairat Sasa - Fahrun Yamin; Iswadi M. Ahmad; Irfandi R. Hi. Mustafa (Academy of Social Science and Global Citizenship Journal, 2026)
From the results of observations that researchers carried out on March 10 2026 it was found that 52% of students came from the number of class VIII students, namely 23 students did not work on assignments in the Integrated Social Sciences subject. This study aims to find out and analyze the efforts of social studies subject teachers in instilling the character of discipline and student responsibility through integrated social studies learning in class VIII Salafiyah Alkhairat Sasa. This research uses qualitative research methods. The analysis technique used in this research is descriptive analysis technique. the results of the study found that social studies teaching efforts in instilling the character of discipline and responsibility, namely throughprinsip Contextual teaching and learning (CTL) in which the teacher relates the material he is studying using students' concrete global situations. Some of the obstacles in cultivating the character of discipline and responsibility include a) family factors, b) environmental factors, c) bold learning, d) factors originating from the students themselves. Meanwhile, the solution to obstacles in cultivating the character of discipline and responsibility is through, a) Control by the head of the Islamic Boarding School, b) the active role of the teacher.